Women's health, public policy, and community action - Mukhopadhyay, Swapna; National Seminar on Women's Health and Reproduction (1995 : India International Centre) (New Delhi : Manohar Publishers & Distributors, 1998)
Contributed articles presented at the National Seminar on Women's Health and Reproduction held at India International Centre, New Delhi in Nov. 1995; with special reference to Indian women.
Includes bibliographical references and index.
Keywords: Women's health services -- India -- Political aspects -- Congresses; Women's health services -- India -- Social aspects -- Congresses; Non-governmental organizations -- India -- Congresses